Factor completely 16x8 − 1. (4x4 − 1)(4x4 1) (2x2 − 1)(2x2 1)(4x4 1) (2x2 − 1)(2x2 1)(2x2 1)(2x2 1) (2x2 − 1)(2x2 1)(4x4 − 1).

Respuesta :

The factors of the expression specified is given by: Option B: [tex](2x^2 - 1)(2x^2 + 1)(4x^4 + 1)[/tex]

What are some basic properties of exponentiation?

If we have a^b then 'a' is called base and 'b' is called power or exponent and we call it "a is raised to the power b" (this statement might change from text to text slightly).

Exponentiation(the process of raising some number to some power) have some basic rules as:

[tex]a^{-b} = \dfrac{1}{a^b}\\\\a^0 = 1 (a \neq 0)\\\\a^1 = a\\\\(a^b)^c = a^{b \times c}\\\\ a^b \times a^c = a^{b+c} \\\\^n\sqrt{a} = a^{1/n} \\\\(ab)^c = a^c \times b^c[/tex]

What is the product result of (a+b)(a-b) ?

Suppose two numbers are there as 'a' and 'b'.

Then, we get:

[tex](a+b)(a-b) = a(a-b) + b(a-b) = a^2 -ab + ab - b^2 = a^2 - b^2\\(a+b)(a-b) = a^2 - b^2[/tex]

For the considered case, factoring the considered expression [tex]16x^8 - 1[/tex] by rewriting it as:

[tex]16x^8 - 1 = (4 \times 4 \times x^4 \times x^4) - 1^2 = (4x^4)^2 -1^2\\\\\\[/tex]

Now, since we've got [tex](a+b)(a-b) = a^2 - b^2[/tex], therefore,

[tex]16x^8 - 1 = (4x^4)^2 -1^2\\16x^8 - 1 = (4x^4 +1 )(4x^4 - 1)[/tex]

The second term can also be factored using same property, as shown below:

[tex]16x^8 - 1 = (4x^4 +1 )(4x^4 - 1) = (4x^4 + 1)((2x^2)^2 - 1^2) \\16x^8 - 1 = (4x^4 + 1)(2x^2 + 1)(2x^2 - 1)\\\\\text{Rearranging the terms, we get}\\16x^8 - 1 = (2x^2 - 1)(2x^2 + 1)(4x^4 + 1)[/tex]

Therefore, the factors of the expression specified is given by: Option B: [tex](2x^2 - 1)(2x^2 + 1)(4x^4 + 1)[/tex]

Learn more about exponentiation here:

https://brainly.com/question/15722035

Answer:

Option B

Step-by-step explanation:

I took the test.